Three new species of horned frogs, Megophrys (Amphibia: Megophryidae), from northeast India, with a resolution to the identity of Megophrys boettgeri populations reported from the region - Mahony, Stephen; Teeling, Emma C.; Biju, S. D. (Zootaxa, 2013)
Northeast India is a well-established region of biological importance but remains poorly understood with regards to the species level identifications of many of its extant amphibians. In this study we examined small sized frogs from the genus Megophrys recently collected from remote and suburban forests in the northeast Indian states of Meghalaya and Arunachal Pradesh, from which we have identified three new species. Megophrys vegrandis sp. nov., Megophrys ancrae sp. nov. and Megophrys oropedion sp. nov. are compared with all known congeners from India and surrounding regions from which they differ based primarily on a combination of morphological characters. Megophrys boettgeri is removed, and Megophrys minor added to the Indian amphibian checklist, through critical review of all literature pertaining to the former species, and the discovery of an overlooked historical report of the latter species. Two of the new species, Megophrys ancrae sp. nov. and Megophrys vegrandis sp. nov. are known from low and mid elevations within two large protected forests in Arunachal Pradesh, both with poorly studied amphibian fauna. Contrastingly, Megophrys oropedion sp. nov. is currently known only from small forested areas on the upper reaches of the Shillong Plateau. The importance of the Shillong Plateau as an area of known high amphibian endemicity is highlighted in the light of the miniscule proportion of its land area afforded government protection, raising concerns about the future conservation of its still poorly known species.